Identifying the factors affecting the extraction of phenolic compounds in wine production - Fataliyev, Hasil; Heydarov, Elnur; Ismayilov, Mehman; Gadimova, Natavan; Baloghlanova, Konul; Fataliyeva, Shabnam (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is red grape varieties rich in phenolic compounds, the wine samples obtained from them, and the physicochemical and mechanical means used during the extraction process. Although several studies have been conducted on the extraction of phenolic compounds into juice and wine, the impact of mechanical methods-based on maceration for different durations, alcoholic extraction at various degrees of darkness, thermal treatment, enzyme preparations, and agitation-on extraction, as well as the effect of different storage conditions on the total content of phenolic compounds and anthocyanins, has not been studied. In the case of the Khindogni variety, during alcoholic treatment of the pomace up to 6% alcohol, phenolic compounds were not distinctly perceptible. The experimental wine material showed higher color intensity in pomace treated with 10% and 18% alcohol than the control. Comparison of different methods (thermal, enzyme preparations, etc.) indicated that enzymatic treatment (Trenol Color DF, dose 2.0 mg/dm3) provided more efficient extraction. Agitation increased the extraction of phenolic compounds by more than 1.24 times. During 6 months of storage, the mass concentration of phenolic compounds in Syrah wine material decreased by 21.3%, and anthocyanins decreased by 16.4%. The problem of producing red wines rich in phenolic compounds and anthocyanins is addressed through the application of physicochemical and mechanical methods, including alcoholic extraction of pomace for varying maceration periods, thermal treatment, enzyme and agitation effects, and storage under different conditions. The obtained results can be applied in winemaking operations.